Impact of novel coronavirus pandemic on aquaculture and fisheries in developing countries and sustainable recovery plans: Case of Bangladesh. (September 2021) - Islam, Md Monirul; Khan, Makidul Islam; Barman, Aparna
Abstract: Like most sectors, the aquaculture and fisheries sector especially in developing countries like Bangladesh is believed to have been severely affected by this unique coronavirus (COVID-19) pandemic. To overcome the adverse impacts of COVID-19, the aquaculture and fisheries economy needs urgent recovery plans which this study focusses on using a mixed-method including online questionnaire surveys, face-to-face and telephonic interviews and focus group discussions during June – November 2020. This study reveals some positive impacts on ecosystem and fish stock (e.g., increase in fish stock) due to less disturbance of fishing activities, but that are not able to bring societal benefits as all the fisheries sub-sectors are affected differently by the pandemic. There are disrupted transportation systems and increased transportation costs (around 20 – 60% higher than normal), more input and maintenance costs and less demand for/and decreased market price of fish. There are also shortages of labourers and reduced patrolling to implement fishery regulations. Cancellation of orders by foreign buyers has seriously affected the shrimp and crab sub-sectors. The fisheries-dependent people's capital assets and activities have been mostly negatively affected resulting in a worsened livelihood. This study has suggested a set of immediate and long-term changes to policy and action plans to recover this sector and sub-sectors from the pandemic considering economic, social and environmental sustainability. The findings of this study may have important implications not only for Bangladesh but also for other fisheries dependent developing countries with similar impacts by the virus like in South Asia. Highlights: COVID-19 resulted significant negative impacts on aquaculture and fisheries. Fisheries-dependent people's livelihood assets and activities are negatively affected. Positive impacts on ecosystem and wild fish stock. Recovery process includes immediate and long-term action plans. Recovery needs to consider economic, social and environmental sustainability.